Synthesis of manganese diboride by microwave assisted method - D. H. Davtyan (ՀՀ ԳԱԱ հրատ.)
Nanosized powder of manganese diboride (MnB2) was synthesized by the microwave heating method for the first time. A stoichiometric mixture of manganese dioxide (MnO2) and magnesium dodecaboride (MgB12) was used as raw material, where magnesium dodecaboride served as the reducing agent and a source of boron. A domestic microwave oven was used to generate microwave radiation. Phase composition of the initial mixture and the obtained product were examined by XRD studies, of the initial mixture and formation of a single-phase final product, MnB2. Average particle size of synthesized manganese diboride (40 nm) was calculated on the basis of Scherer’s formula. Առաջին անգամ միկրոալիքային վառարանային եղանակով սիթեզվել են մանգանի դիբորիդի (MnB2) նանոփոշիներ, օգտագործելով մանգանի երկօսիդի (MnO2) և մագնեզիումի դոդեկաբորիդի (MgB12) ստեխիոմետրիկ բաղադրությամբ ելային խարնուրդը: Մագնեզումի դոդեկաμորիդը կիրառվել է որպես վերականգնիչ և բորի աղբյուր: Իբրև միկրոալիքի աղբյուր կիրառվել է կենցաղային միկրոալիքային վառարանը: Միկրոալիքային սինթեզի տևողությունը կազմել է 10 րոպե: Ռենտգենաֆազային ուսումնասիրությունների հիման վրա ցույց է տվել, որ տեղի է ունենում ելանյութերի լրիվ փոխարկում: Սինթեզված մանգանի դիբորիդի նանոհատիկների միջին չափսը գնահատվել է Շերերի հայտնի բանաձևով և կազմել է 40 նմ: Впервые методом микроволнового нагрева синтезированы нанопорошки диборида марганца (MnB2). В качестве исходных веществ была использована стехиометрическая смесь диоксида марганца (MnO2) и додекаборида магния (MgB12). Последний служил как восстановитель и одновременно источник бора. Нагрев реагирующей смеси осуществлялся в бытовой микроволновой печи. Продолжительность микроволнового синтеза составляла 10 мин. Рентгенофазовым анализом установлено полное превращение исходных веществ. Средний размер частиц (40 нм) синтезированного диборида марганца оценен по известной формуле Шерера.
Keywords: Inorganic Chemistry; Physical Chemistry